2000
DOI: 10.1007/s004149900114
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial findings in fatal carbon monoxide poisoning: a human and experimental morphometric study

Abstract: The aim of this study was to define the status of the myocardium in selected human cases of acute, fatal carbon monoxide intoxication and the myocardial changes in rats exposed to carbon monoxide in relation to the type of cardiac arrest and the effects of reoxygenation following pre-fatal CO intoxication. The human study consisted of 26 cases (17 accidental and 9 suicide) of acute, fatal CO intoxication, without evidence of obstructive coronary atherosclerosis or history of ischemic heart disease which were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…In the present study, the only myocardial lesion found corresponded to "contraction band necrosis" or "coagulative myocytolysis" or "Zenker necrosis": the two latter terms prove to be more precise due to the presence of different types of contraction bands and they indicate a necrosis of the myocardial cells in a hypercontracted state (tetanic death) characterised by rhexis of the myofibrillar apparatus, anomalous hypereosinophilic cross-bands formed by segments of hypercontracted sarcomeres with extremely thickened Z lines, as shown ultrastructurally [32,33,34,35]. Within chronological limits, the present findings confirm the conclusions of the previous human study [7]: a. Cocaine-related adrenergic overactivity does not induce extensive myocardial necrosis and thus per se is unable to explain the cardiac arrest.…”
Section: Morphological Findingsmentioning
confidence: 95%
“…In the present study, the only myocardial lesion found corresponded to "contraction band necrosis" or "coagulative myocytolysis" or "Zenker necrosis": the two latter terms prove to be more precise due to the presence of different types of contraction bands and they indicate a necrosis of the myocardial cells in a hypercontracted state (tetanic death) characterised by rhexis of the myofibrillar apparatus, anomalous hypereosinophilic cross-bands formed by segments of hypercontracted sarcomeres with extremely thickened Z lines, as shown ultrastructurally [32,33,34,35]. Within chronological limits, the present findings confirm the conclusions of the previous human study [7]: a. Cocaine-related adrenergic overactivity does not induce extensive myocardial necrosis and thus per se is unable to explain the cardiac arrest.…”
Section: Morphological Findingsmentioning
confidence: 95%
“…The incidence of non-lethal CO poisoning is not well established nor is that of unrecognized CO poisoning (subacute poisoning). Also, there are some reports on myocardial morphologic changes in acute CO poisoning, especially stressing the importance of contraction bands (Fineschi et al 2000;Baroldi et al 2001).Melatonin is a pineal hormone, and also commercially available as over-the-counter for use in hope of rejuvenation. Melatonin affects the heart by direct and indirect ways (Pang et al 2000;Sewerynek 2002).…”
mentioning
confidence: 99%
“…The incidence of non-lethal CO poisoning is not well established nor is that of unrecognized CO poisoning (subacute poisoning). Also, there are some reports on myocardial morphologic changes in acute CO poisoning, especially stressing the importance of contraction bands (Fineschi et al 2000;Baroldi et al 2001).…”
mentioning
confidence: 99%
“…For instance, contraction band necrosis is absent in carbon monoxide intoxication, whether accidental or suicidal, suggesting an antiadrenergic effect of lethal anoxia despite a longer survival period. Only if reoxygenation is restored, contraction bands lacking interstitial hemorrhage will be present (30). In other words, we need to know the frequency, extent, and stages of this lesion to interpret both the natural history of a disease and the mode of death.…”
Section: The Myocardial Alterationmentioning
confidence: 99%